Global company and EU Impact of EU Economic Policy on Doing Business - Vrabec, Michal; Urban, Luděk, 1927-2013; Czesaný, Slavoj, 1940-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
This master thesis tests the statement whether the EU Economic Policy related to the Internal Market Project decreases the costs of doing business or not. We tested the conducting of business of Global Company in seven various regions (Visegrad Countries, Baltic, East Balkan Countries, Croatia, Russia, Ukraine and Turkey). We framed the research period into 2011 and focused on four major Research Fields (Transportation, Cross-border Trading, Consumer Protection and Financial Regulation). Based on the cost impact analysis we could confirm that Internal Market Project decreases the costs of doing business.
Vedoucí práce: Luděk Urban
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses